Elephant Grass Silage with Pelleted Citrus Pulp: Chemical Composition, Digestibility, and Feedlot Costs - Barbosa, C. R.; Santos, M. M. E.; Meirelles, P. R. L.; Torres, R. N. S.; Baldassini, W. A.; Costa, C. (Faculty of Animal Science, IPB University, 2025)
This study aimed to assess the effects of including pelleted citrus pulp (PCP) in BRS Capiaçu elephant grass silage on its chemical composition and digestibility and the production costs of feedlot diets for beef cattle. A completely randomized experimental design in a 2×5 factorial scheme was used considering 90- and 120-day harvesting intervals for ensiling and five inclusion levels of PCP (0%, 3%, 6%, 12%, or 24% as fed). The dry matter (DM) content of the silages increased with regrowth interval (p<0.01) and there was a quadratic response to the inclusion level of PCP (p<0.01). Total digestible nutrients of the silages decreased with increasing Capiaçu regrowth interval (p<0.01) but increased linearly with increasing inclusion levels of PCP during ensiling (p<0.01). The in vitro DM digestibility of silage increased linearly with the inclusion of PCP (p<0.01) and with increasing regrowth interval (p<0.01). The inclusion of PCP and grass regrowth interval linearly increased DM recovery from silage (p<0.01). Adding up to 24% PCP during the ensiling of Capiaçu improves the fermentation profile and nutritional value of the silage and digestibility parameters. Based on economic analysis, we recommend the use of silage prepared from Capiaçu harvested at 120 days and containing 6% to 12% PCP because of its lower cost per unit of gain (/arroba produced), cost per animal, and total feedlot costs compared to the other treatments.